Sudden death associated with lipoma of the cerebellopontine angle - Stefano Tambuzzi; Guendalina Gentile; Michele Boracchi; Arnaldo Migliorini (Autopsy and Case Reports, 2022)
Intracranial lipomas are rare benign tumors considered exceptional when localized in the cerebellopontine angle (CPA), with an incidence of 0.1% of the total number of expansive processes located in this area. We present a case of the sudden death of a 26-year-old young woman in which an unencapsulated neoformation of 0.8 cm was documented at the right cerebellopontine angle and was histologically characterized as intracranial lipoma. The cause of death was then identified as a cardiocirculatory failure secondary to supratentorial (uncal right) herniation caused by the lipoma of the pontocerebellar angle with high-grade diffuse cerebral edema.